A systematic review of the subfamily Syringophilinae (Acari: Syringophilidae) of the Nearctic region. Part 1: quill mites associated with passerines (Aves: Passeriformes) - Skoracki, Maciej; Spicer, Greg S.; Oconnor, Barry M. (Zootaxa, 2016)
Quill mites belonging to the subfamily Syringophilinae Lavoipierre, 1953 associated with the Nearctic passeriform birds are revised. All of the 49 known species, which are grouped in seven genera, are recorded. Among them, four new species are described: Syringophiloidus audubioni sp. nov. from Spizella breweri (Cassini) (Emberizidae), Syringophilopsis catesbyi sp. nov. from Vireo olivaceus (Linnaeus) (Vireonidae), S. wilsoni sp. nov. from Pheucticus melanocephalus (Swainson) (Cardinalidae), and S. bartrami sp. nov. from Spizella passerina (Bechstein) (Emberizidae). The species Syringophilopsis hylocichlae Clark, 1964 syn. nov. is synonymized with Syringophilopsis turdus (Fritsch, 1958), and Syringophiloidus zonotrichia syn. nov. is synonymized with Betasyringophiloidus seiuri (Clark, 1964) comb. nov. Six species are recorded from the Nearctic region for the first time: Syringophiloidus delichonum Bochkov, 2001, S. glandarii (Fritsch, 1958), S. weiszii Skoracki et al., 2001, S. bombycillae Skoracki, 2002, Syringophilopsis mimidus Sikora et al., 2011, and Torotrogla merulae Skoracki et al., 2000. Data on Nearctic syringophiline species, their hosts and distribution are summarized and the keys to all species are constructed.